Iowa Birdline update, November 29, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for November 29, 1993. Highlights include reports for Long-tailed Duck, two Scoter species, Western Grebe, Golden Eagle and Snowy Owl. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed